Management of Competency Development for Islamic Religious Education Teachers in the Use of Learning Media at the Rahmat Islamiyah Foundation in Medan - Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to analyze the management of competency development for Islamic religious education teachers in the use of learning media at the Rahmat Islamiyah Foundation in Medan. This research uses qualitative research methods, with a phenomenological type. Data was obtained using several data collection methods, namely: observation, interviews, and documentation. Then the data was analyzed using the Miles Huberman interactive analysis model, with four stages: 1) data collection; 2) data reduction; 3) data presentation; 4) Drawing conclusions and verifying data. The technique used to guarantee the validity of the data is using triangulation. The results of the research show that schools manage the development of teacher competency in the use of learning media, namely by: 1) providing development training to teachers; 2) motivate teachers to innovate learning, especially in the use of learning media; 3) supervise every teacher who teaches; 4) carry out evaluations and provide rewards.